SIR JOHN GARDNER WILKINSON (1797-1875): LOST WORLDS OF ANTIQUARIANISM IN EGYPT AND THE BALKANS - Frost, Robert (2022)
This project takes an “intellectual history” or “history of ideas” approach toward reconsidering the work of Sir John Gardner Wilkinson (1797-1875), who has been referred to as “the father of British Egyptology”. Existing interpretations of the history of archaeology and Egyptology in the early 19th century are exclusively dominated by a focus on the race to decipher hieroglyphs, the discovery of tombs and the scramble for collecting antiquities, a state of affairs which are presented as giving way to “scientific” archaeology as the 19th century progressed. However, I argue that Wilkinson, and other early 19th-century scholars, pioneered an antiquarian approach, borrowing from a strong antiquarian tradition of scholarship widespread in 18th and 19th century Britain, and that they were interested in an array of research questions, which extended well beyond hieroglyphs and antiquities. Whereas later Egyptian archaeology focused on excavation and reconstructing individual site histories, Wilkinson studied classical texts and indigenous Egyptian material culture to gain insights. Rather than studying Egyptian antiquities and monuments in isolation, he sited them in their original context, thus demonstrating a high degree of spatial awareness. This is notably evident in two of his research projects. First, Wilkinson was interested in ascertaining the former extent of the ancient Egyptian empire in Nubia and Asia. This depended on fieldwork which was contingent upon the location of antiquities and monuments: temples, fragments of temples, boundary stones and ancient frontier fortresses. When Wilkinson was denied access to such sources, he turned to relief scenes of temples such as the Ramesseum and Medinet Habu, to reconstruct ancient Egyptian history and geography. Second, Wilkinson conducted geomorphological research into the nature of the ancient Egyptian environment, which he then used to draw conclusions about Egyptian prehistory and economic development – an approach that was only rediscovered in the late 20th century. To further upset the current narrative, Wilkinson, and other antiquarian colleagues, showed that the first stratigraphic excavation, supported by leading professional scientists such as Lyell and Darwin, relied on highly problematic assumptions. Finally, in addition to his work in Egypt, Wilkinson undertook an extended research programme in Dalmatia and Montenegro, in the Balkans. Here, he carried over his antiquarian approach, of giving equal emphasis to texts and material sources, in an investigation of the classical topography of the region, its history, and its peoples: the last of these also drew on romantic antiquarianism, conditioned by classical sources.